Developing a Hydrologic Monitoring Network in Data‐Scarce Regions Using Open‐Source Arduino Dataloggers. Issue 1 (1st April 2016) - Hund, Silja V.; Johnson, Mark S.; Keddie, Tom
Abstract : Core Ideas: An innovative low‐cost open‐source Arduino‐based datalogger was developed. The datalogger was deployed for hydrologic monitoring in tropical watersheds. Arduino datalogger performance was robust after overcoming initial challenges. The system has great potential for automated continuous environmental monitoring. Continuous hydrologic monitoring is limited in many regions of the world, creating serious knowledge gaps for water resources managers and scientists. Recent advances in open‐source software and hardware technologies, such as the Arduino project, show potential for the development of low‐cost (∼$100) automated dataloggers required for continuous data collection. We developed an Arduino‐based datalogger (the Ecohydro Logger) coupled with water sensors providing digital output to establish a hydrologic monitoring network in the data‐scarce wet‐dry tropics of Guanacaste, Costa Rica. While we experienced some challenges with a first iteration of our Arduino‐based datalogger, an improved version was robust and able to capture long periods of high‐frequency stream discharge data. Integration of the monitoring program into the local community was also key to successful deployment, allowing exchange of local knowledge and support. The accessible and low‐cost nature of Arduino‐based dataloggers can provide a means to extend continuous environmental monitoring into data‐scarce regions.